Pengaruh Nilai Tukar dan Inflasi pada Reksadana Syariah di Indonesia - Hartati, Yuliana Eva; Kismawadi, Early Ridho; Hamid, Abdul; Mardhiah, Ainun (Universitas Islam Negeri Sunan Kudus, 2021)
The increasing development of Islamic mutual funds and making a more varied and more promising sharia capital market instrument for investors who want to invest their capital in the Islamic capital market, are able to make Indonesia the largest country in establishing a sharia capital market. However, the development of Islamic mutual funds is not easy to make the largest sharia-based investment container in Indonesia because there are still many factors that can affect the rise and fall of NAVs in Islamic mutual funds that Investment Managers still find difficult to overcome. The purpose of this study is to analyze the factors that influence the development of Islamic mutual funds in Indonesia. In this study the data used is secondary data. Data obtained from various sources, namely part of the Indonesia Stock Exchange (BEI) Annual Report and also a portion of the Sharia Mutual Fund Development Statistics in the Financial Services Authority (OJK) and Bank Indonesia (BI) taken in the third quarter of 2015-Quarterly III 2018. Data were analyzed using multiple linear regression methods and using SPSS software. The results obtained showed that partially Islamic NAV mutual funds were only influenced by inflation and the number of RDS, while the Jakarta Islamic Indeks and the exchange rate did not affect the NAV of Islamic mutual funds. Simultaneously shows that Jakarta Islamic Indeks, exchange rate, inflation and the amount of RDS have a simultaneous influence on the dependent variable (Islamic mutual fund NAV.